Hubungan Ketuban Pecah Dini Dengan Kejadian Asfiksia Pada Bayi Baru Lahir Di RSUI PKU Muhammadiyah Delanggu - Anna Uswatun (Stikes Muhammadiyah Klaten, 2021)
Asphyxia is a condition in which a newborn cannot breathe spontaneously and regularly which is characterized by hypoxemia, hypercarbia and acidosis. The infant mortality rate in Klaten Regency in 2018 was 10.77 / 1000 live births. The absolute number of infant deaths is 170 out of 15,786 live births. Of the 170 infant deaths, 68 infant deaths were caused by Low Birth Weight (LBW), 15 deaths caused by asphyxia, 46 deaths caused by congenital disorders, 5 deaths caused by sepsis, 1 death caused by pneumonia, 3 deaths caused by diarrhea, and 32 death from other causes. The research objective was to determine the relationship between premature rupture of membranes and the incidence of newborn asphyxia. This type of research is an analytic survey with a cross time approach. The population of this study were 44 people with premature rupture of membranes and asphyxia of newborns in RSUI PKU Muhammadiyah Delanggu in 2019. The sampling technique used was non-probability as many as 44 people. The data collection tool used documentation sheets. Data analysis was performed using Chi-square. The results showed that 37 infants (54%) mild asphyxia, 6 infants (14%) moderate asphyxia, 1 infant (2%) severe asphyxia and 36 mothers (82%) had no to 8 mothers (18)%. The conclusion in this study is that there is no relationship between premature rupture of membranes and the incidence of newborn asphyxia at RSUI PKU Muhammadiyah Delanggu with a value of p = 0.397 (p <0.05). Health workers and the government should work together in order to improve the quality of health services to prevent premature rupture of membranes and asphyxia of newborns and for further research it is hoped that research can be carried out with primary data.